Comparison of Somatostatin Analogue (SA) and Chemotherapy (CT) in Neuroendocrine Tumors (NET) Patients with Ki-67 ?20% - Ozaslan, E.; Koca, S.; Sevinc, A.; Hacioglu, B.; Ozcelik, M.; Duran, A. O.; Ciltas, A. (Karger, 2016)
[Abstract Not Available]
13th Annual ENETS Conference for the Diagnosis and Treatment of Neuroendocrine Tumor Disease -- MAR 09-11, 2016 -- Barcelona, SPAIN
Keywords: Somatostatin analogue; NET; Ki-67